2017
DOI: 10.3201/eid2306.161950
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Hemorrhagic Fever in Migrant Worker Returning from Oman to India, 2016

Abstract: In January 2016, a migrant worker who returned home to India after becoming ill in Oman was confirmed to have Crimean-Congo hemorrhagic fever (CCHF). Physicians should include CCHF in the differential diagnosis for patients with hemorrhagic signs and a history of recent travel to any area where CCHF is endemic or prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…This is the first study to describe the complete sequence of the S segment ORFs of a series of CCHFV isolates from the region. The results largely confirm findings from partial sequencing of sporadic isolates from the UAE [19,28] and Oman [10,27] since the mid 1990's. The phylogenetic relationship of these sequences with other published sequences from the region is depicted in Figure 4.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is the first study to describe the complete sequence of the S segment ORFs of a series of CCHFV isolates from the region. The results largely confirm findings from partial sequencing of sporadic isolates from the UAE [19,28] and Oman [10,27] since the mid 1990's. The phylogenetic relationship of these sequences with other published sequences from the region is depicted in Figure 4.…”
Section: Resultssupporting
confidence: 79%
“…Limited data are available on the prevalent clade(s), or group(s) of organisms from a single ancestor, of CCHFV in the Arabian Peninsula. Sequencing of the S, M, and L segments of CCHFV isolated from the 1996 patient in Oman (recorded as Oman 1997 in GenBank) showed that it belonged to Asia lineage 1 (clade IV) [10,26], as was the virus isolated from a patient who returned to India with CCHF acquired in Oman in 2016 [27]. Virus isolates from 4 patients in the UAE in 1994 and 1995 also align with the Asia 1 (clade IV) lineage, as did contemporaneous isolates from Hyalomma ticks obtained from livestock imported into the UAE from Somalia [9,19,28].…”
Section: Introductionmentioning
confidence: 99%
“…Limited data are available on the prevalent clade(s), or group(s) of organisms from a single ancestor, of CCHFV in the Arabian Peninsula. Sequencing of the S, M, and L segments of CCHFV isolated from the 1996 patient in Oman (recorded as Oman 1997 in GenBank) showed that it belonged to Asia lineage 1 (clade IV) [10,26], as was the virus isolated from a patient who returned to India with CCHF acquired in Oman in 2016 [27]. Virus isolates from 4 patients in the UAE in 1994 and 1995 also align with the Asia 1 (clade IV) lineage, as did contemporaneous isolates from Hyalomma ticks obtained from livestock imported into the UAE from Somalia [9,19,28].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, CCHF has emerged or re-emerged in several countries often with dramatically increased case numbers. Furthermore, there has been a marked increase of imported cases of CCHF in European and South Asian countries [13][14][15][16][17]. The root causes of the increased CCHF incidence rates are not fully understood, but factors such as shifts in climate patterns, animal and human migratory patterns, population increase in livestock and wildlife accompanied by changes in agricultural practices and increased land use may be responsible [18,19].…”
mentioning
confidence: 99%